Comparative Analysis of Metaphysical Approaches to Consciousness Problem - Naghdyan, Ruben (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
The article seeks to analyze the problem of psychic origin and existence from the perspectives of metaphysical approach. It presents the comparative analysis of three metaphysical concepts of A. E. Mirakian, V. M. Allakhverdov and M. B. Mensky. The article shows that the solution to fundamental problems of psychology inevitably leads to the question of the world structure and reality. A. I. Mirakian’s metaphysical approach is related to the definition and overcoming “product” approach, which leads to the need of going beyond the ranges of reality of psychic phenomena. V. M. Allakhverdova’s metaphysical approach is based on Karl Popper’s “World of Propensities”, while M. B. Mensky’s metaphysical approach generated from the quantum concepts about the world structure, which holds certain place in the consciousness.